Dune, outcrop, and pan sediments from the southern Kalahari Basin: A geoarchaeological case study from the Kgalagadi district, Botswana - Inez Faul; Taylor Grandfield; Stefan Dreibrodt; Sarah Mothulatshipi; Phillip Segadika; Christopher Green; Marine Frouin; Michaela Ecker (Southern African Field Archaeology, 2025)
Research from the southern Kalahari Basin (previously considered to be of limited Pleistocene archaeological significance) has provided evidence of human occupation. Surveys and excavations conducted in the Kgalagadi District near Tsabong in south-western Botswana have revealed a plethora of archaeological evidence. The region includes geomorphological features, including dunes, low quartzite hills, and pans. Duricrust formations are visible inside the pans. Previous research suggests that the pans form in topographical low points and likely already existed during the Pleistocene, while lunette dunes accumulated from deflated pan sediment during recent drying periods. However, in this region, these features have not been analysed in a geoarchaeological context, which can provide insight into the formation of archaeological sites. We investigated the mechanisms involved in the deposition of pan, dune, and sandy outcrop sediment by applying a multi-method analysis to thirty sediment samples. Analysis of pan samples reveals the presence of mostly intergrade duricrusts, with some calcretes present. Pan sediment containing fragmented ostracod valves in juvenile instars indicates post-mortem transport (taphocoenosis), and along with the diatoms (Campylodiscus sp.), are indicative of a brackish to saline water body. Inner dune samples share more similarities with pan sediments than with the red sand samples, as they contain higher concentrations of calcium oxide and some contain calcite and sepiolite. Particle size distributions change from unimodal in the outcrops and red dunes, to polymodal in the pans, suggesting that runoff during the wet season contributes to site formation. Sediment deflation by wind contributed to artefacts being exposed on the surfaces of the outcrops. This study therefore identifies three main site formation processes, namely deflation, runoff, and various duricrust formations, which provides insights into the environmental and climatic conditions that influenced human habitation in the Kalahari.